Food and nutrition security in transforming Ghana: A descriptive analysis of national trends and regional patterns - Ecker, Olivier; van Asselt, Joanna (International Food Policy Research Institute, 2017)
In recent decades, Ghana has experienced high economic growth and transformation, which contributed to the nation achieving the Millennium Development Goal targets on reducing extreme poverty and hunger. Against this background and in view of achieving the food and nutrition security targets of the Sustainable Development Goals, Ghana started a process of reviewing its food security and nutrition strategies and policies, including the overarching Zero Hunger Strategy. This discussion paper aims to contribute to this process by providing an update on the state of Ghana’s food and nutrition security. In addition to providing an overview of long-term historical trends at the national level, this analysis provides an overview of regional patterns of food and nutrition insecurity and recent changes across Ghana’s 10 administrative regions. Finally, the analysis identifies regional “hot spots” of food and nutrition insecurity. This paper confirms that Ghana has achieved substantial improvements in food and nutrition security overall, especially over the past decade. Nationwide, progress has been made in improving households’ economic access to food by reducing poverty and extreme poverty and in reducing chronic and acute child undernutrition. However, progress in reducing micronutrient malnutrition—particularly anemia and especially among young children—has been more modest. Across Ghana, large rural-urban gaps and regional differences—mainly between the north and the south—remain for most dimensions of food and nutrition security. In addition, Ghana is increasingly facing new nutrition-related public health problems that result from overnutrition and diets too rich in calories. Overweight and obesity among adults are rising rapidly in both urban and rural areas, leading to an increase in the risk of noncommunicable diseases. The rising double burden of malnutrition—that is, the coexistence of overnutrition and undernutrition, including micronutrient deficiencies—constitutes a challenge to public health and social protection policy. These new nutritional realities may make some existing food and nutrition security policies obsolete or even detrimental to nutrition security.